2020
DOI: 10.1021/acs.analchem.0c01253
|View full text |Cite
|
Sign up to set email alerts
|

Radiofluorinated Smart Probes for Noninvasive PET Imaging of Legumain Activity in Living Subjects

Abstract: Overexpression of legumain is closely associated with tumor proliferation, invasion, and metastasis. Because of its intrinsic properties, such as high sensitivity and resolution, positron emission tomography (PET) has become an effective imaging technique for early diagnosis, treatment response prediction, and monitoring. Herein, two legumain-targeting radiofluorinated smart probes ( 18 F-2 and 18 F-3) as well as a control probe ( 18 F-1) were specifically designed for PET imaging of legumain activity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 22 publications
0
22
1
Order By: Relevance
“…S18, ESI †). It was found that the Michaelis constant (K m ) of MAAN was 72.5 mM, which was lower than that of another legumain-responsive compound (K m = 266.29 mM) reported previously by our group, 33 indicating that MAAN possessed higher sensitivity toward legumain.…”
Section: Esi †)contrasting
confidence: 70%
See 1 more Smart Citation
“…S18, ESI †). It was found that the Michaelis constant (K m ) of MAAN was 72.5 mM, which was lower than that of another legumain-responsive compound (K m = 266.29 mM) reported previously by our group, 33 indicating that MAAN possessed higher sensitivity toward legumain.…”
Section: Esi †)contrasting
confidence: 70%
“…32 In our recent work, two legumain-targeted radiotracers were used for the noninvasive visualization of legumain in tumors via positron emission tomography (PET) imaging. 33 Given the high tumor specificity exhibited in animal models of these probes, legumain could be used as a potential target for cancer therapy. To our knowledge, TRT based on legumain has rarely been reported up to now.…”
Section: Introductionmentioning
confidence: 99%
“…Until the present work was accomplished, there were no AEP imaging studies reported in the field of neurodegenerative diseases. Previous imaging probes were primarily applied to tumors to explore the role of AEP in tumor progression and metastasis [ 42 , 43 ]. To the best of our knowledge, we here showed for the first time that up-regulated AEP in AD brain can be monitored by live-animal imaging analysis.…”
Section: Discussionmentioning
confidence: 99%
“…So far, a large number of probes have been reported for the detection of legumain [ 6 , 11 , 13 , 19 , 20 , 21 , 22 , 23 , 24 ]. In 2015, Liang and co-workers reported a nuclear magnetic resonance (NMR) probe for imaging legumain in HEK293T tumor-bearing zebrafish [ 20 ].…”
Section: Introductionmentioning
confidence: 99%